2009
DOI: 10.1002/elan.200804451
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Cadmium and Lead Complexes with Low Molecular Weight Organic Acids

Abstract: The Cd and Pb complexes with oxalic (OA) and citric acid (CA) were detected in model and soil solutions using cyclic and stripping voltammetry. A mixed complex consisting of Cd, Pb, and OA was found; its peak potential varied from À 582.0 to À 542.5 mV (vs. Ag/AgCl/KCl(3 mol L À1 )). For mixed complex formation, the presence of PbOH þ species and Cd 2þ in oxalic acid solution was necessary. Only the simple complexes of CA with Pb and Cd were found in the model solution. The existence of all investigated metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Molecular orbital calculations show that aldehyde derivative of 1 has lower LUMO energy than diflunisal 1 [E LUMO (aldehyde of 1) = -2.54 eV was calculated]. It is in agreement with the fact that aldehydes are more easily reduced than corresponding carboxylic acids [16]. Aldehydes are known to occur in their hydrated form.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Molecular orbital calculations show that aldehyde derivative of 1 has lower LUMO energy than diflunisal 1 [E LUMO (aldehyde of 1) = -2.54 eV was calculated]. It is in agreement with the fact that aldehydes are more easily reduced than corresponding carboxylic acids [16]. Aldehydes are known to occur in their hydrated form.…”
Section: Resultssupporting
confidence: 53%
“…Electrochemical methods are frequently employed as a part of biomimetic modelling of reductive drug metabolism [14]. Biological redox reactions occur in lipid double layer of biological membranes; organic compounds in non-aqueous solvents can be used as a medium for modelling studies [15][16][17]. To the best of our knowledge, the only few electrochemical studies about diflunisal [1,2] reported in the literature concern the optimization of methods for its determination in several biological matrices, and no previous study has been published on the mechanism of reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The level of adsorption is directly related to the organic matter content, structure/complexity and pH of the soil [8]. The characterization of adsorption on organic soil matter is complicated due to high level of variability of the soil matter structure and content [9,10]. On the other hand, the adsorption level depends on the pH value as well.…”
Section: Introductionmentioning
confidence: 99%
“…A soil solution used as a representative biological matrix was prepared from a forest soil [37], sampled according to the methodology described in [30,38]. The selection of suitable supporting electrolyte (SE) is essential for the proper functionality of the electrochemical device.…”
Section: Chemicals and Sample Preparationmentioning
confidence: 99%